2014
DOI: 10.4269/ajtmh.13-0640
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin Concentration and Parasitemia on Hospital Admission Predict Risk of Multiple Organ Dysfunction Syndrome among Adults with Malaria

Abstract: Abstract. Risk factors for progression from acute malaria to multiple organ dysfunction syndrome (MODS) are poorly understood. The MODS is commonly diagnosed with the sequential organ failure assessment (SOFA) scale, but this scale has been understudied in patients with severe malaria. We conducted a cohort study among 426 adult males admitted to hospital with malaria in Bogotá, Colombia. We estimated SOFA scores and relative risks (RRs) for MODS during hospitalization according to patients' characteristics on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Glucocorticoids are considered to be the most effective anti-inflammatory drugs (21), but their therapeutic role in sepsis remains controversial, particularly regarding the proper dose of them. A large number of clinical studies have determined that the concentration of inflammatory factors in low in the blood of sepsis patients receiving hydrocortisone (22,23). Furthermore, glucocorticoids are immunosuppressive agents, and different degrees of immune function inhibition may occur in the course of application.…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticoids are considered to be the most effective anti-inflammatory drugs (21), but their therapeutic role in sepsis remains controversial, particularly regarding the proper dose of them. A large number of clinical studies have determined that the concentration of inflammatory factors in low in the blood of sepsis patients receiving hydrocortisone (22,23). Furthermore, glucocorticoids are immunosuppressive agents, and different degrees of immune function inhibition may occur in the course of application.…”
Section: Discussionmentioning
confidence: 99%
“…There is a need to predict the complications in the stable pretreatment stage. A retrospective study of patients admitted for malaria showed that hemoglobin and parasitemia at admission predicted subsequent multiple organ dysfunction syndrome (MODS); however, the study did not exclude complicated cases at admission [13]. Intra-neutrophilic pigments correlate well with parasitemia and severity of complications, but the utility of this finding has not been studied in an uncomplicated pretreatment setting.…”
Section: Introductionmentioning
confidence: 98%
“…Asexual reproduction of Plasmodium falciparum occurs mainly in the erythrocytes. The high density of Plasmodium in severe malaria patients can lead to multiple organ dysfunction [ 3 ]. In this study, 12 patients who met the diagnostic criteria for severe malaria [ 4 ] were treated with exchange transfusion 14 times, as well as a conventional anti-malarial treatment.…”
Section: Introductionmentioning
confidence: 99%